Slavery in Harriet Beecher Stow’s Uncle Tom’s Cabin: One of the Causes of The American Civil War, 1861 – 1865 - Maizufri Maizufri (LINGUA LITERA : journal of english linguistics and literature, 2015)
The History of the Civil War has been told and told again, but sometimes people are always forgetting this bad memory. This article, however, tries totrace back the American Civil War’s description in 1861-1865; its purpose is to remind us about its historical importance. Unlike George Washington, Abraham Lincoln also became a super-hero as a result of that war. What have they accomplished? Furthermore, this article also discusses their major accomplishments through one of the American literary works, Uncle Tom’s Cabin, written by Harriet Beecher Stowe as one of the causes of that Great War.